Sengketa Blok Ambalat Antara Indonesia-Malaysia - Arie Samuel Ngahu; Jeremias petrik ghode; Damianu Bria; Yohanes Arman (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
Indonesia and Malaysia are two countries that have historically disputed with each other. One of the disputes between Indonesia and Malaysia is the Ambalat Block boundary dispute. The Ambalat Block is a sea area of ​​15,235 square kilometers which is in the Sulawesi Sea or the Makassar Strait. The Ambalat Block is estimated to contain oil and gas that can be utilized for decades to come. Ambalat, is near the border line of Indonesia and Malaysia. In this area as a fishing area in Sebatik waters. This water area is recorded to be rich with potential for reef and demersal fish. Ambalat is not only rich in fish potential. This area, which is located in North Kalimantan, has long been a dispute between Indonesia and Malaysia. One of them, because it has the potential of oil and natural gas. Geological Survey Center - Geological Agency of the Ministry of Energy and Mineral Resources (ESDM) has identified this potential. Based on G&G study data around the East Ambalat area, this potential is in the Tarakan basin and its surroundings. The naming of the marine block contained in the Ambalat block is based on the interests of exploring marine and underwater wealth, especially in the oil mining sector. Tensions between Indonesia and Malaysia are increasing due to the ownership claims of each country over the Ambalat block area, the Ambalat block area which is now a dispute between the States of Indonesia-Malaysia is not a land area but is located at a sea depth of 2500 meters on the continental shelf geographically, block Ambalat is a natural continuation of the Indonesian Kalimantan mainland which is in the Tarakan Basin spreading area which has the potential as oil and gas.